2016
DOI: 10.1111/jerd.12272
|View full text |Cite
|
Sign up to set email alerts
|

Morphological Simulation of Different Incisal Embrasures: Perception of Laypersons, Orthodontic Patients, General Dentists and Orthodontists

Abstract: Incisal embrasures play an important role in smile esthetics and influence the attractiveness perception. In general, the semi-rounded embrasure form is the most preferred. Different groups' perceptions on tooth morphology reinforce the importance of patient participation in treatment planning. (J Esthet Restor Dent 29:68-78, 2017).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 29 publications
0
4
0
Order By: Relevance
“…For the higher scores, orthodontists gave significantly lower scores than prosthodontists and laypersons. This result may be attributed to the fact that orthodontists routinely use facial analysis and smile analysis during treatment planning and diagnosis [ 29 – 31 ], which makes them more critical for identifying smaller levels of deviations compared to other dentistry professionals and laypersons, as shown by previous studies [ 4 , 12 , 13 , 15 , 22 ]. Other studies have shown that orthodontists tend to be stricter in their evaluations and give lower mean scores [ 1 , 4 , 12 , 13 , 18 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For the higher scores, orthodontists gave significantly lower scores than prosthodontists and laypersons. This result may be attributed to the fact that orthodontists routinely use facial analysis and smile analysis during treatment planning and diagnosis [ 29 – 31 ], which makes them more critical for identifying smaller levels of deviations compared to other dentistry professionals and laypersons, as shown by previous studies [ 4 , 12 , 13 , 15 , 22 ]. Other studies have shown that orthodontists tend to be stricter in their evaluations and give lower mean scores [ 1 , 4 , 12 , 13 , 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…Since esthetic treatment procedures frequently involve the anterior esthetic zone and require a multidisciplinary team approach, the different specialists involved should share their knowledge regarding smile esthetics among one another, which would facilitate communication and would improve the treatment outcome [4,11]. There are several studies that have compared the opinions of orthodontists, general dentists, and lay people regarding smile esthetics [1,4,5,[12][13][14][15][16][17][18]. However, to the best of our knowledge, no study has compared the opinions of orthodontists, prosthodontists, and laypersons regarding the vertical positions of anterior teeth and smile esthetics.…”
mentioning
confidence: 99%
“…Numerous studies have been undertaken about how laypeople and professionals in dental medicine interpret smiles [ 1 , 2 , 3 , 4 , 5 ]. Kokich et al found that orthodontists, doctors of dental medicine, and laypeople have different perceptions of specific dental esthetic discrepancies [ 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…They are considered the most pleasing when they are semi-rounded in shape, and this is exactly what is found in conical and ovoid teeth. Squared incisal embrasures are considered un-esthetic, especially among the female population [ 5 ]. When discussing the incisal portion of dental crowns, it is important to note that different people perceive the relationship between the length of the central and lateral incisors differently (incisal step).…”
Section: Introductionmentioning
confidence: 99%
“…Although the tooth is considered to be the basic component of smile design, the "incisal embrasure's" role cannot be overlooked as a smile is more considerably affected by a small change in the embrasures rather than the change in the tooth anatomy itself 4 . Teeth shapes play an important role in esthetics and influence the pattern of the incisal embrasure 5 . Incisal embrasure is the divergence formed by the proximal surfaces of anterior teeth from the contact point initially.…”
Section: Introductionmentioning
confidence: 99%